Dual Antibiotic and Diffusible Signal Factor Combination Nanoliposomes for Combating Staphylococcus epidermidis Biofilm - Golara Gerayelou; Bahman Khameneh; Bizhan Malaekeh-Nikouei; Asma Mahmoudi; Bibi Sedigheh Fazly Bazzaz (Tabriz University of Medical Sciences, 2021)
Purpose: Microbial biofilms are one of the main causes of persistent human infections. Encapsulation of an antibiotic and a biofilm dispersal agent within a nano-carrier has been recognized as a novel approach to combat the problem of biofilm-related infections. Here, we develop the nanoliposomal formulation for delivery of vancomycin in combination with cis-2- decenoic acid (C2DA), to Staphylococcus epidermidis biofilm. The effects of the formulations were studied at two stages: biofilm growth inhabitation and biofilm eradication. Methods: Liposomal formulations were prepared by the solvent evaporation dehydration-rehydration method and were evaluated for size, zeta potential, and encapsulation efficacy. The ability of different agents in free and encapsulated forms were assessed to evaluate the anti-biofilm activities. Results: Vancomycin and C2DA were successfully co-encapsulated in the same nanoliposome (liposomal combination). The zeta potential values of the liposomal formulations of vancomycin, C2DA, and the liposomal combination were 37.2, 40.2, 51.5 mV, and the mean sizes of these liposomal formulations were 167.8±1.5, 215.5±8.8, 235.5±0.01, respectively. Encapsulation efficacy of C2DA was 65% and about 40% for vancomycin. The results indicated that liposomal combination exerted strong anti-biofilm activities, slightly exceeding those observed by the free form of a combination of vancomycin and C2DA, but higher than either agent used alone in their free forms. The anti-biofilm activity of formulations followed concentration and time-dependent manner. Conclusion: The combination of vancomycin and C2DA could inhibit biofilm formation. Employing the liposomal combination is a considerable method to remove bacterial biofilm.